Short-term Response in Molecular and Biochemical Adaptation of White Shrimp (Litopenaeus vannamei) Postlarvae Reared in A Biofloc System - Yasa, Ngurah Sedana; Anshory, Lutfi; Triastutik, Gemi; Murwantoko, Murwantoko; Isnansetyo, Alim; Lusiana, Lusiana (Aquacultura Indonesiana, 2019)
Up regulation of heat shock proteins (HSPs) in organisms can be detected in response to many kinds of stressor. Recently there were few studies have focused on the three kinds of heat shock proteins (HSPs) and antioxidant enzyme activity after biofloc stress. The objective of this study was to investigate the effect of different biofloc volume on the expressions of (LvHSP60, LvHSP70, and LvHSP90), the activity of superoxide dismutase (SOD) and phenoloxidase (PO) of the L. vannamei after biofloc addition. PL10 L. vannamei were divided into three groups: precondition, biofloc stress (5mL/L, 10mL/L, 15mL/L), and recovery. The gene expression results showed that the expressional levels of LvHSP60, LvHSP70, and LvHSP90 were increased significantly in 6h treatment and tend return to normal conditions after 48h treatment. Superoxide dismutase activity was reduced during treatment and phenoloxidase activity was elevated slightly after 12h to 24h and tend to pretreatment level at recovery periods. All of these HSPs expression reverted to normal levels 6h after the recovery period. The results indicated that different expression patterns of the three HSPs. HSP60 have a longer and higher protection expression after 12h treatment than HSP70 and HSP90. HSP90 was more sensitive in 6h at all treatments than HSP60 and HSP70. It is concluded that supplementation of biofloc with the volume of 5-15mL/L caused Hsp protection in L. vannamei PLs at the first 6h to 48h treatment and increased phenoloxidase activity at 24-48h treatment and reduced survival rate of the white shrimp.